A study on resonance characteristics of a microstrip open-loop resonator - Görür, A; Karpuz, C; Yilmaz, A; Yalçin, K (JOHN WILEY & SONS INC, 2001)
A microstrip open-loop resonator (MOLR) is proposed for maximum miniaturization in microwave applications, and to obtain a wider upper stopband including the first spurious resonance frequency for planar bandpass filters. The effect of variation in the width of one of the longer strips of an OLR formed in two ways (namely, fired-gap (FG) and variable-gap (VG) OLR) on their resonance characteristics is discussed. Also, simple empirical expressions indicating the effect of variation in the strip width are derived for estimation of the resonance frequency as a function of the variable strip width and the fundamental resonance frequency of the standard loop resonator. (C) 2001 John Wiley & Sons, Inc.
Keywords: open-loop resonators; slow-wave structures; FILTERS; Engineering; Optics